Synthesis of new copper(i) based linear 1-D-coordination polymers with neutral imidazolinium-dithiocarboxylate ligands1. Issue 12 (11th February 2015) - Neuba, A.; Ortmeyer, J.; Konieczna, D. D.; Weigel, G.; Flörke, U.; Henkel, G.; Wilhelm, R.
<x xml:space="preserve">Abstract</x> An imidazolinium-dithiocarboxylate betaine has been applied for the first time as a ligand in a coordination polymer with copper(i) halides.